Synthetic Difference-in-Differences Estimation - Damian Clarke; Daniel Paila\~nir; Susan Athey; Guido W. Imbens (Institute of Labor Economics (IZA), 2023)
In this paper, we describe a computational implementation of the Synthetic difference-in-differences (SDID) estimator of Arkhangelsky et al. (2021) for Stata. Synthetic difference-in-differences can be used in a wide class of circumstances where treatment effects on some particular policy or event are desired, and repeated observations on treated and untreated units are available over time. We lay out the theory underlying SDID, both when there is a single treatment adoption date and when adoption is staggered over time, and discuss estimation and inference in each of these cases. We introduce the sdid command which implements these methods in Stata, and provide a number of examples of use, discussing estimation, inference, and visualization of results.
Keywords: C13; C87; C23; C52; C63; 330; difference-in-differences; synthetic control; synthetic difference-in-differences; estimation; inference; visualization